The mains controller / Hasnah Hassan and Zainah Mansoh - Hassan, Hasnah; Mansoh, Zainah (1986)
This project is primarily designed for use with a home computer to enable it to control pieces of mains powered electrical or electronic equipment. It operates by sending a signal through the mains supply so that no connecting wires from the controller unit to the receivers are necessary. The system should work well between any two room of a house and an outbuilding, providing that they are on the same mains circuit. System of this type are not suitable for long distdnce though. fhe controller can be used with up to four receivers and each receiver has a relay that control mains loads of up 10 Amps. for some 2400 Watts with the 240 Volts UK mains voltage. The used of phase locked loop tone decoder device in each receiver largely accounts for this combination of simplicity and reliability. The controller can be driven directly from any computer, such as the VIC 20 and spectrum computers. This project was built with two parts, a transmitter and a receiver. The transmitter and the receiver are operated through AC mains lines and are controlled by the computer. All the data needed are already programmed from the computer.